THE EFFECT OF INDEPENDENCE AND COMPETENCE ON THE EFFECTIVENESS OF THE INTERNAL CONTROL SYSTEM WITh AUDITOR'S WORK EXPERIENCE AS A MODERATION VARIABLE AT THE INSPECTION OFFICE OF PT BANK RAKYAT INDONESIA, Tbk. MEDAN REGION - Alhamdi, Ridha; Siregar, Saparuddin (CV. Radja Publika, 2022)
This study aims to examine the effect of independence and competence on the effectiveness of the internal control system, the effect of independence and competence together on the effectiveness of the internal control system, and whether the work experience of internal auditors can moderate independence and competence on the effectiveness of the internal control system at the Inspection Office of PT. Bank Rakyat Indonesia. Tbk Medan Region. The population of this research is 45 auditors spread over 5 working areas of the Inspection Office of Bank Rakyat Indonesia, Tbk Medan Region. The data used in this study is primary data collected through a questionnaire. The respondents of this study were internal auditors. Testing research data using multiple linear regression analysis and residual test for moderating variables. The results of this study indicate that: 1) Partially, the independence of internal auditors affects the effectiveness of the internal control of the Inspection Office of PT Bank Rakyat Indonesia (Persero), Tbk. Medan Region; 2) Partially, the competence of internal auditors affects the effectiveness of the internal control of the Inspection Office of PT Bank Rakyat Indonesia (Persero), Tbk. Medan Region; 3) Simultaneously, the independence and competence of internal auditors have a positive and significant effect on the effectiveness of internal control. This is because the independence and competence of internal auditors are interrelated elements that must be carried out by internal auditors to improve the effectiveness of internal controls at the Inspection Office of PT Bank Rakyat Indonesia (Persero), Tbk. Medan Region; 4) Work experience is not proven to moderate (strengthen or weaken) the independence and competence of the effectiveness of internal control at the Inspection Office of PT Bank Rakyat Indonesia (Persero), Tbk. Medan Region.